Institutional infrastructure and economic growth in OIC countries - Mohd Ali, Ly Slesman @ Sulaiman; Baharumshah, Ahmad Zubaidi; Ra'ees, Wahabuddin Sahibuddin (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
This paper investigates the relationship between qualities of institutional infrastructure and economic growth in a panel of 39 Organization of Islamic Countries (OIC). Based on generalized method of moments (GMM) system estimators, we find that better qualities of political and economic institutions exert positive and statistically significant effect on economic growth. Better qualities of the dimensions of political institutions ensuring stable government, less expropriations, and low external conflicts with other countries. The empirical results also reveal that when these political and economic institutions are accounted for, institutions preventing internal conflicts and tensions arising from ethnic and religious conflicts have no significant impacts on the long-run growth. Thus, institutional and structural reforms target towards upgrading the qualities of political and economic institutions are crucial for long-run growth.